1994
DOI: 10.1007/bf00700634
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biodegradation of phenanthrene in a biphasic culture system

Abstract: Degradation of phenanthrene by Pseudomonas aeruginosa AK1 was examined in (i) an aqueous mineral salts medium to which phenanthrene particles of varying size (i.e. diameter) were added, and (ii) an aqueous/organic biphasic culture system consisting of mineral salts medium supplemented with 2,2,4,4,6,8,8-heptamethylnonane (HMN) as the phenanthrene-carrying organic phase. In both systems, the rate of phenanthrene biodegradation could be significantly enhanced by manipulations leading to improved phenanthrene mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 30 publications
4
17
0
Order By: Relevance
“…Presumably, mass transfer of hexadecane from the matrix to the bulk solution is enhanced by mixing, especially for matrices with large pores, but cannot be further enhanced by rhamnolipid or another surfactant under conditions of intense agitation. A similar dependence on hydrodynamic conditions was found for the effect of surfactants on the biodegradation of phenanthrene present as crystals or dissolved in an organic phase by P. aeruginosa (Kö hler et al, 1994). Under conditions of low agitation, surfactant addition stimulated degradation but under conditions of high agitation surfactants failed to further stimulate biodegradation.…”
Section: Release Of Hexadecane From the Matricessupporting
confidence: 67%
“…Presumably, mass transfer of hexadecane from the matrix to the bulk solution is enhanced by mixing, especially for matrices with large pores, but cannot be further enhanced by rhamnolipid or another surfactant under conditions of intense agitation. A similar dependence on hydrodynamic conditions was found for the effect of surfactants on the biodegradation of phenanthrene present as crystals or dissolved in an organic phase by P. aeruginosa (Kö hler et al, 1994). Under conditions of low agitation, surfactant addition stimulated degradation but under conditions of high agitation surfactants failed to further stimulate biodegradation.…”
Section: Release Of Hexadecane From the Matricessupporting
confidence: 67%
“…These data and the microscopic observations revealed that yeasts grew in Significantly better adaptation was observed in the consortium in relation to each species alone in the biphasic assays; moreover, phenol presence incremented the interfacial associated cells and the biodegradation of hydrophobic organic pollutants as was shown by other authors (Köhler et al 1994;Owen et al 1997). …”
Section: Debaryomyces Castellisupporting
confidence: 76%
“…It was hypothesized that solubilization of benzo-[a]pyrene was a necessary step in the overall biodegradation process because benzo[a]pyrene bioavailability to the consortium organisms was increased. Increased bioavailability of target hydrophobic compounds to degrading organisms is an integral part of the biodegradation of these compounds, especially PAHs (18,32).…”
Section: Resultsmentioning
confidence: 99%